PASAR SYARI'AH DAN KESEIMBANGAN HARGA - Marhamah Saleh (Sharia and Law Faculty, 2011)
The market is an economic indicator of a country. In the concept of a modern economic, market mechanism is largely determined by supply and demand. But long time ago the classical moslem scholars such as Abu Yusuf, Yahya ibn Umar, Al-Ghazali, Ibn Taymiyya and Ibn Khaldun had voiced several factors that help forming a market mechanism, and also about the government policy in order to market intervention and price regulation. In the normal economic circumstances, the government is not justified to interfere to determine prices and affect the market mechanism. But when the monopoly practices (ihtikar), hoarding (iktinaz), political dumping (siyasah al- ighraq), and various fraud committed by marketeer, the government is proposed to control the prices in order to achieve the benefit of the people. This article comparatively tries to observe the past opinions of Moslem economists about market behavior in accordance with the sharia and the creation of price stability.